Pengaruh Word Of Mouth (Wom) Terhadap Keputusan Pembelian Pada Toko Shoes Holic Yang Terdapat Di Sumatera Barat - Erizal Nazaruddin; Renada Amalia; Nadra Nadila Hutasuhut; Muhammad Fajar Aqla Maulana; Suryadi Irwan (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2024)
Shoes Holic, a well-known shoe retailer in West Sumatra, with locations in the important cities of Bukittinggi, Payakumbuh, and Padang. In a competitive market, businesses must have a competitive advantage to influence customers' purchasing choices. This research will look at how customer recommendations influence their decision to buy shoes from West Sumatra shoe stores. With a sample of 30 people, this study used non-probability sampling techniques and purposive sampling approaches. In this study, simple linear regression was used to test the data. Research findings show that sales at Holic Shoes stores in West Sumatra can be influenced by consumer recommendations.